Acceptance of international criminal justice in Bosnia and Herzegovina (Law and Safety, 2024)
When the XIV Winter Olympic Games took place in Sarajevo in 1984, nobody expected that war would begin only seven years later and kill hundreds of thousands of people living in the former Yugoslavia. That millions of them would be ethnically cleansed and displaced, most of them for good. That hundreds of mass graves would be scattered around, and that war crimes unseen in Europe since the Second World War would be repeated. That severe crimes like systematic rape, torture, and massive destruction of cultural heritage and property would finally culminate with genocide. Consequently, Bosnia and Herzegovina (and the countries of the former Yugoslavia) triggered an immense boost in international criminal law and international criminal justice. That experience, during and after the war that took place from 1992 to 1995, can offer lots of valuable input. Not everything that had been done was good or perfect, but it was of great importance for the further development of international criminal law and international criminal justice in a world that is still searching for appropriate responses to the grave war crimes that occur every day, and for the development of mechanisms and practices that will ensure justice for victims and society and be perceived as such. The atrocities of the Bosnian War served as a wake-up call for the international community, highlighting the urgent need for mechanisms to hold perpetrators of such heinous crimes accountable. The establishment of the International Criminal Tribunal for the former Yugoslavia marked a significant milestone in this regard, pioneering the prosecution of individuals responsible for genocide, war crimes, and crimes against humanity committed during the conflict. However, challenges persist in ensuring access to justice for all victims and addressing the root causes of conflict to prevent future atrocities. The lessons learned in Bosnia and Herzegovina remain crucial in shaping efforts to achieve lasting peace and accountability worldwide.
Keywords: Bosnia and Herzegovina; justice; criminal justice; war crimes; victims.